Degradation of norfloxacin by calcite activating peroxymonosulfate: Performance and mechanism. (November 2021) - Chu, Ziyang; Chen, Tianhu; Liu, Haibo; Chen, Dong; Zou, Xuehua; Wang, Hanlin; Sun, Fuwei; Zhai, Peixun; Xia, Min; Liu, Meng
Abstract: In this study, calcite was investigated as an activator for the norfloxacin (NOR) degradation by peroxymonosulfate (PMS). Under optimum conditions, the NOR removal percentage was 99.7% within 60 min, and the pseudo-first-order kinetics effectively described the two-stage oxidation process. The NOR removal percentage improved from 10.4% to 91.5% and the reaction rate constant elevated from 0.0010 to 0.1217 min −1 when 0.5 g/L calcite was added compared to that without calcite addition. Furthermore, the results of radical scavenger and electron spin resonance trapping indicated that the favorable alkaline environment and a proper level of carbonate in the Calcite/PMS system facilitated the activation of PMS to generate 1 O2 for rapid NOR degradation. Compared with NaOH, calcite was able to maintain the pH (8–9) of the reaction system stable. Besides, the content of anions with buffering capacity and organic matter in the water matrix influenced the removal percentage of NOR. Seven intermediates were identified and the NOR degradation pathways were suggested. The findings of this research provided an environmentally friendly activator for remediation of organic wastewater and deepened the understanding of the interaction between calcium carbonate and PMS. Graphical abstract: Image 1 Highlights: Calcite efficiently activated peroxymonosulfate (PMS) degrading norfloxacin (NOR). Singlet oxygen was the main reactive species generated in the Calcite/PMS system. Calcite maintained a constant solution pH (8–9). The degradation pathway of NOR was proposed involving seven intermediates.